Pengaruh Work Shift dan Burnout terhadap Performance Masinis PT Kereta Api Indonesia (PERSERO) - Priatna Priatna; Septiana Dwiputrianti; Edah Jubaedah; Hafid Aditya Pradesa; Takaya Hasegawa (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the effect of work shifts and burnout on the performance of train drivers at PT Kereta Api Indonesia (Persero), and compare these findings with fatigue management practices and work systems for train drivers in Japan and China. This study is based on Job Demands–Resources (JD-R) Theory, which explains that job demands, including night shifts and irregular rotations, increase the risk of burnout and decrease performance in high-risk jobs. The study used quantitative methods through PLS-SEM with 2,184 train drivers. The results showed that work shifts had a significant positive effect on burnout (60.8%), and a significant negative effect on train driver performance (33.9%). Burnout also had the strongest influence on performance decline (83.9%), and mediated 51% of the effect of shift work on performance.